Direct water treatment by APGD with rotating electrodes - Golota, V.; Mohanty, P.; Zavada, L. (Problems of Atomic Science and Technology, 2023)
The APGD with rotating star-shaped electrodes was applied directly to the surface of liquid as a counter electrode. It was shown that the rotation of electrodes enables the stabilization of the discharged. A high concentration of H₂O₂ and nitrates were measured. The high level of microbial reduction was shown for inoculated deionized water treated by APGD with rotating electrodes. Використовувався тліючий розряд атмосферного тиску (APGD) між обертовим зіркоподібним електродом і поверхнею води в якості другого електрода. Показано, що обертання електродів дозволяє стабілізувати розряд. Була зафіксована висока концентрація H₂O₂ та нітратів. Високий рівень мікробного зменшення було показано для інокульованої деіонізованої води, обробленої APGD з обертовими електродами.